2012
DOI: 10.1371/journal.pone.0035739
|View full text |Cite
|
Sign up to set email alerts
|

Connection between Telomerase Activity in PBMC and Markers of Inflammation and Endothelial Dysfunction in Patients with Metabolic Syndrome

Abstract: Metabolic syndrome (MS) is a constellation of metabolic derangements associated with vascular endothelial dysfunction and oxidative stress and is widely regarded as an inflammatory condition, accompanied by an increased risk for cardiovascular disease. The present study tried to investigate the implications of telomerase activity with inflammation and impaired endothelial function in patients with metabolic syndrome. Telomerase activity in circulating peripheral blood mononuclear cells (PBMC), TNF-α, IL-6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 34 publications
5
42
0
5
Order By: Relevance
“…Asymmetric dimethyl arginine (ADMA) is linked to the impairment of endothelial NO-dependent function, by inhibiting endogenous nitric oxide synthetase in a concentration dependent manner, and has been associated with cardiovascular diseases (Boger et al, 1998;Palomo et al, 2011). The pathophysiology of insulin resistance involves pro-inflammatory cytokines, altered adipokines and endothelial dysfunction (Rentoukas et al, 2011;Tsarouhas et al, 2011). Moreover, dyslipidemia is a major risk factor for development of several obesity-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric dimethyl arginine (ADMA) is linked to the impairment of endothelial NO-dependent function, by inhibiting endogenous nitric oxide synthetase in a concentration dependent manner, and has been associated with cardiovascular diseases (Boger et al, 1998;Palomo et al, 2011). The pathophysiology of insulin resistance involves pro-inflammatory cytokines, altered adipokines and endothelial dysfunction (Rentoukas et al, 2011;Tsarouhas et al, 2011). Moreover, dyslipidemia is a major risk factor for development of several obesity-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Their result apparently confirms that threshold effect is related to telomere length and cellular senescence. Another study performed by Rentoukas et al (2012) to reveal the effect of telomerase in patients with inflammation and impaired endothelial function found that patients with metabolic syndromes had significant telomerase activity in their circulating PBMC. These results suggested that prolonged inflammation could act as a pathway in atherosclerosis resulted from diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Длительное хроническое воспаление приво-дит к истощению теломеразы, что мы и наблюдали у пациентов с СД2. При менее выраженном и менее длительном хроническом воспалении, как это имеет место при метаболическом синдроме или умерен-ном атеросклерозе, напротив, наблюдается увели-чение активности теломеразы [20], что, вероятно, носит компенсаторный характер, замедляя умень-шение длины теломер в активно делящихся клетках …”
Section: Discussionunclassified